Insular Christianity : alternative models of the Church in Britain and Ireland, c.1570-c.1700 - Armstrong, Robert (Robert Matthew); Ó hAnnracháin, Tadhg (Manchester : Manchester University Press, 2013)
This focused collection of essays on the alternative establishments which both Presbyterians and Catholics attempted to create in Britain and Ireland offers a dynamic new perspective on the evolution of post-reformation religious communities within Britain and Ireland.
Alternative establishments? Insular Catholicism and Presbyterianism / Robert Armstrong and Tadhg Ó Hannracháin -- 'Replant the uprooted trunk of the tree of faith' : the Society of Jesus and the continental colleges for religious exiles / Thomas M. McCoog -- 'Genevan Jesuits' : crypto-Presbyterianism in England / Polly Ha -- Riots, rescues and 'grene bowes' : Catholics and protest in Ireland, 1570-1640 / Clodagh Tait -- Authority, agency and the reception of the Scottish National Covenant of 1638 / Laura A.M. Stewart -- The influence of the Irish Catholic clergy in shaping the religious and political allegiances of Irish Catholics, 1603-1641 / David Finnegan -- Politics and religion in the Westminster assembly and the 'grand debate' / Chad Van Dixhoorn -- Coping with alternatives : religious liberty in royalist thought 1642-1647 / Anthony Milton -- 'The remembrance of sweet fellowship' : relationships between English and Scottish Presbyterians in the 1640s and 1650s / Ann Hughes -- An alternative establishment : the evolution of the Irish Catholic hierarchy, 1600-49 / Tadhg Ó Hannracháin -- The Irish alternative : Scottish and English Presbyterianism in Ireland / Robert Armstrong -- The laity and the structure of the Catholic Church in early modern Scotland / R. Scott Spurlock -- Between Reformation and Enlightenment : Presbyterian clergy, religious liberty and intellectual change / John Coffey.
Online resource; title from home page (viewed on Apr. 12, 2013).
Includes bibliographical references and index.
JSTOR
Keywords: Catholic Church -- Great Britain -- History -- 17th century; Catholic Church -- Ireland -- History -- 17th century; Catholic Church -- History -- 17th century; Église catholique -- Histoire -- 17e siècle.; Catholic Church; Katholische Kirche; Presbyterian Church -- Great Britain -- History -- 17th century; Presbyterian Church -- Ireland -- History -- 17th century; Église presbytérienne -- Grande-Bretagne -- Histoire -- 17e siècle.; Église presbytérienne -- Irlande -- Histoire -- 17e siècle.; Presbyterian Church; Great Britain; Ireland; Presbyterianer; Großbritannien; Irland; 1600-1699; Electronic books; History